(untitled) (KONFERENSIYA, 2025)
This scientific article examines the pragmatic features of small-genre texts (headlines, slogans, advertisements, labels, social media microtexts) in translation. Using functional-pragmatic theory, the research analyses how communicative intent, cultural meaning, emotional impact, and persuasive strategies are preserved or adapted in Russian translations. The paper demonstrates that pragmatic equivalence outweighs literal correspondence in small-genre translation and highlights the importance of functionalist approaches such as Scopes theory and dynamic equivalence. The results show that effective translation requires localization, compensation, transcreation, and close attention to speech acts, implicatures, and genre conventions.